2001
DOI: 10.1128/iai.69.7.4647-4653.2001
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Properties of the Streptococcus intermedius Surface Protein Antigen I/II

Abstract: Streptococcus intermedius is associated with deep-seated purulent infections. In this study, we investigated expression and functional activities of antigen I/II in S. intermedius. The S. intermedius antigen I/II appeared to be cell surface associated, with a molecular mass of approximately 160 kDa. Northern blotting indicated that the S. intermedius NCTC 11324 antigen I/II gene was transcribed as a monocistronic message. Maximum expression was seen during the early exponential phase. Insertional inactivation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
42
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 54 publications
3
42
0
1
Order By: Relevance
“…In our study we investigated directly the role of the CSP signal in biofilm formation and competence development of the wildtype strain. We found that the respective synthetic CSPs favored the biofilm mode of growth for both S. intermedius and S. mutans, and we confirmed the role of CSP in S. intermedius competence development (9,19).…”
Section: Downloaded Fromsupporting
confidence: 68%
See 2 more Smart Citations
“…In our study we investigated directly the role of the CSP signal in biofilm formation and competence development of the wildtype strain. We found that the respective synthetic CSPs favored the biofilm mode of growth for both S. intermedius and S. mutans, and we confirmed the role of CSP in S. intermedius competence development (9,19).…”
Section: Downloaded Fromsupporting
confidence: 68%
“…Initiation of a QS response during competence development is influenced by environmental conditions. For S. intermedius, conditions that support endogenous induction of competence development have been described (9,19). It appears, however, that the growth-dependent requirements for spontaneous competence can in several instances be overcome by addition of synthetic CSP (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, upon dental treatment the organism may enter the bloodstream, which can result in infectious endocarditis. Most oral streptococci, including S. mutans, Streptococcus sobrinus, Streptococcus gordonii, and Streptococcus intermedius, express a family of structurally and antigenically related surface proteins termed antigen I/II with molecular masses ranging from 160 to 215 kDa (13,21,23,30,32). From the N terminus, the polypeptide has an aminoterminal signal peptide, an alanine-rich repeat unit, a variable region, a proline-rich repeat region, a carboxy-terminal walland membrane-spanning region, and an LPXTG wall anchor motif (19,38).…”
mentioning
confidence: 99%
“…The apparently broad binding specificity toward different glycoproteins is, however, not unusual among bacterial adhesins. For example, antigen I and II adhesins of oral streptococci mediate binding to a wide variety of molecules, such as salivary agglutinin, collagen, laminin, and fibronectin, and also to other microorganisms of the oral cavity without any apparent specificity toward a single molecular determinant (28,36,43,44,50). The increased amount of streptococcal pullulanase on the surface of the Rgg-deficient strain NZ131rgg and the increased strepadhesin activity could be due to at least two cellular mechanisms.…”
Section: Vol 71 2003 Glycoprotein Binding and S Pyogenes Pullulanamentioning
confidence: 99%